Effectiveness of Glucocorticoids in the No-Reflow Phenomenon in STEMI Patients - Sokolov, Maksim Y.; Salo, Sergii V.; Shumakov, Valentyn O.; Shpak, Serhii S. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Relevance. The driving force behind the pathogenesis of no-reflow, as a component of ischemic-reperfusion injury, is myocardial edema, which provokes extravascular compression of the infarct-related artery (IRA), making it impossible to restore antegrade blood flow. Targeting edema is a promising approach in the treatment of this condition. Aim. To analyze different strategies for managing no-reflow and to present data on the intracoronary single-dose administration of glucocorticoids in terms of their ability to improve blood flow gradation according to the TIMI scale during primary PCI in STEMI patients. Materials and methods. During the period 2022–2024, 26 STEMI patients with no-reflow (TIMI 0/1 after stent implantation) were selected and divided into two groups of 13 patients each. The main group received a single intracoronary selective injection of methylprednisolone (250 mg) via a microcatheter into the IRA. The control group did not receive intracoronary pharmacotherapy for no-reflow, only hemodynamic support in case of hemodynamic deterioration. Results. The most significant risk factor for the occurrence of no-reflow was found to be a prolonged period of acute myocardial ischemia, which, in our study, lasted 18 hours from the onset of symptoms. Regarding the effect of glucocorticoids, it was observed that when using methylprednisolone, administered according to the approved methodology, an increase in blood flow from TIMI 0 to TIMI 3 was achieved in 61.5% of cases. Compared with the control group, the angiographic effectiveness of this new treatment for the no-reflow phenomenon reached 53.8%. In-hospital mortality did not differ significantly between the two groups (38.46% vs. 53.85%). Conclusions. The duration of acute myocardial infarction symptoms is a crucial risk factor for the no-reflow phenomenon during primary PCI. This study demonstrates that the use of glucocorticoids can help restore blood flow in no-reflow cases. Achieving TIMI 3 blood flow following a single intracoronary injection of methylprednisolone occurred in 61.5% of patients in the treatment group. Compared with the control group, the effectiveness of this new method reached 53.8%. Despite the improvement in TIMI flow, it was not possible to reduce in-hospital mortality in patients receiving hormone therapy.